COMMUNITY KNOWLEDGE OF ELDERLY NEGLECT: A LITERATURE REVIEW - Syarafina, Farah Zhafirah; Pradana, Anung Ahadi (Universitas Airlangga, 2022)
Introduction: Neglect is a condition when the elderly are unable to meet their needs and do not get help from their family or the surrounding community. This condition is in line with the increasing prevalence of the elderly, as well as the number of neglect of the elderly due to a lack of public knowledge. Methods: The method in writing this article is through a literature review with a simple approach with 10 articles related to the description of the level of public knowledge about elderly neglect in the 2015-2021 period. Results: From 10 articles it was found that the level of public knowledge about neglect in the elderly was categorized as quite low, in terms of understanding in defining the concept of violence in the elderly comprehensively. There are several categories of neglect by the community towards the elderly. And there is still a lack of awareness that is owned by the community in treating the elderly so that it can be called in the elderly adjustment. Conclusions: More knowledge and awareness is needed in treating the elderly in order to prevent neglect of the elderly in order to reduce the prevalence and improve care for the elderly who are in the surrounding environment.